Policy Analysis of Ministerial Regulation No. 24/2007 on Primary School Facilities and Infrastructure Standards: Implications for Education Quality - Nurulita, Aprilia; Rabiah, Vira Muthia (Proceeding International Conference on Religion, Science and Education, 2025)
In Indonesia, the gap in the quality of educational facilities and infrastructure is a serious challenge that has a direct impact on the quality of education. In an effort to address this, the Minister of National Education Regulation No. 24/2007 regulates the minimum standards of infrastructure that must be met by each school to support the learning process. This policy encourages educational institutions to be more concerned with the availability of supporting facilities in order to create a comfortable learning environment for students. This research uses a literature review approach to analyze the policy and its implications for the quality of education in Indonesia. Although this policy has set standard criteria, the actual conditions in the field, especially in schools in remote areas, are still far from expectations. Many schools suffer from classroom shortages, empty libraries, lack of books and learning resources, dysfunctional laboratories, and learning media such as teaching aids, computers and supporting technology are often not available in sufficient quantities. This condition indirectly affects the quality of education. Therefore, the fulfillment of minimum standards of facilities and infrastructure is crucial in creating an educational environment that supports quality improvement, while reducing the gap between schools in developed and underdeveloped areas.